Numerical investigations on charge motion and combustion of natural gas-enhanced ammonia in marine pre-chamber lean-burn engine with dual-fuel combustion system. (8th April 2023) - Wu, Xuefei; Feng, Yongming; Xu, Guodong; Zhu, Yuanqing; Ming, Pingjian; Dai, Liming
Abstract: Ammonia, an efficient hydrogen carrier with the advantages of lower storage cost and higher stability comparing to hydrogen, is becoming a potential solution for carbon dioxide emission reduction from marine engine. In this paper, the CH4 /NH3 mechanism applied to simulate the combustion process of elevated-pressure engine was experimentally verified. Then, simulations were conducted on a marine pre-chamber lean-burn engine to investigate the feasibility of dual-fuel combustion with natural gas and ammonia. The results show that the combustion of the rich mixture ignited by spark in the pre-chamber produces high-speed turbulent jet flames into the main chamber, which promotes the combustion of the lean gas mixture. Additionally, an anomalous pre-ignition pressure rise is observed at 50% natural gas addition. Finally, the performance evaluation of engine indicates that for the design of marine dual-fuel engine, the ammonia fraction range of 50%∼80% should be employed to achieve good engine thermal efficiency. Highlights: Ignition characteristic of the CH4 /NH3 mixtures was studied. Gas mixture formation in the pre-combustion chamber was analyzed. Combustion of lean main mixture was improved by rich-burn pre-combustion chamber. Anomalous pre-ignition pressure rise in the cylinder at 50% natural gas addition. Ammonia fraction range was evaluated to achieve high engine efficiency.